2013
DOI: 10.1002/ajmg.a.35711
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations among people with Down syndrome: A nationwide population‐based study in Denmark

Abstract: SummaryBackground-Most persons with Down syndrome (DS) now survive to adulthood, but their health care needs beyond childhood are not well described. We examined hospitalizations among persons with DS in Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 37 publications
8
33
3
3
Order By: Relevance
“…Another population‐based study from Denmark showed that patients with DS had more than twice the hospitalisation rate and nearly three times hospital days when compared with the general population (Zhu et al . ). Interestingly, when categorising into age groups, the discrepancies were more pronounced during childhood and decreased as patients aged – i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another population‐based study from Denmark showed that patients with DS had more than twice the hospitalisation rate and nearly three times hospital days when compared with the general population (Zhu et al . ). Interestingly, when categorising into age groups, the discrepancies were more pronounced during childhood and decreased as patients aged – i.e.…”
Section: Discussionmentioning
confidence: 97%
“…We found that male patients stayed in the hospital slightly longer than female patients, similar to previously reported (Zhu et al . ). Patients from healthcare‐related facilities presented at later ages than patients who came from home ( N = 22, 52.2 years vs. N = 15, 41.5 years, respectively); this is possibly due to patients with DS transitioning to healthcare‐related facilities from home settings when they become older.…”
Section: Discussionmentioning
confidence: 97%
“…Some, but not all body systems exhibit signs of premature ageing, and, while longevity in people with DS has improved appreciably, age-specific risk for mortality is considerably increased compared with other people with intellectual disabilities [38]. Prior approaches to the description of the distinct clinical profile of adults with DS were based either on population studies based on death certificate diagnoses, or hospital admission diagnoses [11,16,39], or on retrospective series focused on a particular set of disorders (ophthalmologic disorders, cardiovascular disorders, cognitive impairment, celiac disease, etc. ), leading occasionally to contradictory conclusions [23,24,32,33,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, in neurotypical children, the mean delay for a diagnosis of juvenile rheumatoid arthritis/other arthritic conditions was only 0.7 years [23]. The significant health impact of DS is well described throughout the literature and the development of a secondary condition could risk further impairment, not only of physical health and well-being but also of cognitive and/or functional outcome for individuals with DS [24][25][26]. It is the responsibility of the primary care provider caring for the patients with DS to monitor for commonly associated conditions and to provide early diagnosis, intervention and initiation of treatment [27].…”
Section: Discussionmentioning
confidence: 99%